Ingenol mebutate in low amounts for the treatment of actinic keratosis in Korean patients - Joe HJ; Oh BH (Dove Medical Press, 2017)
Hyun Jae Joe, Byung Ho Oh Department of Dermatology, Keimyung University, College of Medicine, Daegu, Republic of Korea Background: Ingenol mebutate (IM), a novel agent for field therapy of actinic keratosis (AK), has a drawback of inducing local skin reactions (LSRs), which may cause discomfort in patients. To reduce the LSRs, we tried the application of IM in low amounts.Objective: The purpose of this study was to review Korean patients with AK being treated with IM and evaluate the LSRs and therapeutic outcomes of low amounts of IM.Methods: We retrospectively reviewed 47 patients with AK on the face. A total of 20 and 27 patients were treated by applying recommended amount of 18.8 mg/cm2 and the lower amount of 10 mg/cm2, respectively.Results: The mean composite LSR score for the low amount group (LAG; 12.18±3.29) was significantly lower than that for the recommended amount group (RAG; 15.45±2.70) (P<0.01, independent sample t-test). The 2-month clearance rate calculated by the number of AKs before and after treatment in each patient was significantly higher for RAG (88.16%), compared with 75.56% for LAG (P<0.001).Conclusion: Low amount of IM for the treatment of facial AK significantly reduced LSRs in Korean patients. Minimizing LSRs may allow for a secondary targeting treatment of IM for the residual lesions, depending on initial treatment outcomes. Keywords: actinic keratosis, field therapy, ingenol mebutate